Gendered implications of COVID-19 on wastewater reuse agri-food value chains in Egypt: Current context and practical recommendations - International Water Management Institute (International Water Management Institute, 2022)
The colonial legacy of irrigated agriculture in Egypt continues to reinforce food security and poverty. Marginalized tenant farmers along the tail end of Drain 7 in Kafr El Sheikh face challenges of polluted, unreliable irrigation water, low crop productivity, income and food insecurity, and poor health. Low value agriculture work is increasingly performed by marginalized women, whose work and time is undervalued and taken for granted. There is no one category of women gendered inequalities are cut across by class, age, education, health – as well as by family ownership of land, location of cultivated plots which determine access to clean or drainage water. Technical changes need to be accompanied by changes in deep-rooted gender-power disparities: women’s ownership of land, their effective engagement in water governance and management requires systemic, structural changes to cultures and practices of and masculinity. COVID19 has made visible the combined social and economic stresses of marginalized women, who struggle with unpaid domestic care work and increasing productive water reuse irrigation, the latter often with little to no social and economic gains.